THE EFFECT OF ERYTHROPOIETIN SUPPLEMENTATION ON SPERM MOTILITY AND MORPHOLOGY IN WISTAR RAT AFTER LIGATION RELEASE OF THE VAS DEFERENS - Pramanta, Aditya; Renaldo, Johan; Soebadi, Doddy M (Indonesian Urological Association, 2019)
Objective: The patency rates after vasectomy reversal ranges from 71-97%, but there is 26-72% possibility of persistent infertility. Dysfunction or obstruction of the epididymis and oxidative stress are thought to be the important cause of male infertility by disrupting spermatozoa maturation process, causing poor sperm quality. Human erythropoietin or better known as EPO is a glycoprotein hormone that has been purified since three decades ago. Research on the EPO has evolved and become a major research topic the researchers aimed as a therapeutic agent. The cloning and expression of erythropoietin has developed recombinant erythropoietin as a drug that serves as an anti-oxidant, anti-apoptotic and anti-inflammatory. This study aimed to determine the effect of erythropoietin supplementation on sperm motility and morphology in Wistar rat after the release of the vas deferens’ ligation. Material & Methods: Twenty four male Wistar rats were randomly divided into four groups (6 each). On the vasectomy group, the vas deferens were serially ligated for 7 weeks using a non-absorbable suture. The vasectomy reversal group get the same surgical treatment and after 7 weeks the ligation were released. While as in the erythropoietin group, recombinant eryhtropoietin (1000 IU/kg) was administered intraperitoneally three times for 1 week after releasing the ligation. Normal control animals received no surgical manipulation and followed by sperm retrieval for analysis. Eosin-stained slides were prepared to assess the motility and morphology of sperm cells and observed under a light microscope. Results: Ligation of vas deferens significantly decreased sperm motility and morphology. Releasing the ligation of the vas deferens did not improve the sperm motility and morphology. Supplementing eryhtropoietin 1000 IU/kg 3 times for a week after releasing the ligation did not improve the sperm motility and morphology. Conclusion: Erythropoietin supplementation did not improve the sperm motility and morphology in Wistar rat after releasing the ligation of vas deferens.